An Evaluation of Social Security Education Programs in Latin America - VERA LÓPEZ, Juana Isabel (Frontera Norte, 2018)
The main goal of this paper is to produce a comparative policy analysis of nine pension systems (Chile, Peru, Colombia, Uruguay, Bolivia, Mexico, El Salvador, Costa Rica, and the Dominican Republic) by reviewing four variables of interest and by analyzing in-depth interviews of officials in charge of supervising pension systems. In this evaluation of pension education programs in Latin America, the experiences of Chile and Uruguay stand out. The study also examines social security education, which helps inform people about their rights and obligations under social security systems.